An economical self-coalescing microfluidic device with an easily observable readout - Kamat, Lily; Delgado, Priscilla; Dissanayaka, Anjana; Myers, David R. (Frontiers in Lab on a Chip Technologies, 2024)
Self-coalescing microfluidicmicrofluidic devices represent an exciting opportunity to leverage viscous dominated flow phenomena to reconstitute a series of reagents with a single sample infusion. In a self-coalescing microfluidicmicrofluidic device, spatially separated dried reagents are reconstituted using a single infusion. Due to the unique device geometry, the reagents remain spatially separated after infusion. As such, self-coalescing microfluidicmicrofluidic devices have the potential to simplify point-of-care testing by simultaneously performing multiple colorimetric tests in one device. The current versions of these devices use standard, more costly microfabrication processes and are too small to be easily read by eye. Here, we created a low cost and scaled up version of a self-coalescing microfluidicmicrofluidic device by using laser cut roll-based silicone tape. In addition to eliminating the need for cleanrooms, our approach simplifies the integration of assay reagents since they can be spotted onto a coverslip and covered with the tape microfluidicmicrofluidic device. We empirically optimized our device, finding that flow rate significantly influenced the formation of self-coalescence as well as proper reagent reconstitution. When flow rates were too slow or fast, reagents would streak, leading to either inadvertent mixing between different spatial locations. Our studies further revealed that geometry more strongly influenced device operation in low-flow conditions. Our final optimized device exhibited a 100% success rate, demonstrated through at both self-coalescence with no reagent streaking at 100 µL/min, which enabled isotropic diffusion of reagents. Further, the spots are spatially separated and large enough to be visualized by the naked eye and captured from a smartphone camera for downstream analysis. Taken together, our innovative device leverages the advantages of sticker microfluidics and low-cost manufacturing methods to offer standalone functionality. This approach has the potential to significantly impact point-of-care diagnostics, particularly in resource-limited regions. By enabling multiplexed diagnostic assays through our novel technology, we aim to provide accessible and affordable healthcare solutions. Taken together, our series of improvements could enable more widespread access to self-coalescing microfluidics especially in low-resource settings.